2021
DOI: 10.1101/2021.12.22.21268226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of observational methods used to quantify personal protective behaviours among members of the public during the COVID-19 pandemic, and the concordance between observational and self-report measures in infectious disease health protection

Abstract: Objectives: To assess the quantity and quality of studies using an observational measure of behaviour during the COVID-19 pandemic, and to narratively describe the association between self-report and observational data for behaviours relevant to controlling an infectious disease outbreak. Design: Systematic review and narrative synthesis of observational studies. Data sources: We searched Medline, Embase, PsychInfo, Publons, Scopus and the Public Health England behavioural science LitRep database from ince… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Similar discrepancies were reported in households with children as well (31% for self-reported vs. 6% for actual) 41 . Discrepancies were also observed in mask-wearing and social distancing, although that in hand disinfection 42 was particularly pronounced. Given that hand sanitization is less likely to disrupt friendships in children than mask wearing, the latter being a concern in psychological studies in terms of emotional recognition 9,[43][44][45] and cognitive performance 46 , replacing some of the mandates for mask-wearing and silent lunches with a greater promotion of hand sanitization might have been an alternative measure to balance the containment of COVID-19 infection and children's well-being.…”
Section: Discussionmentioning
confidence: 89%
“…Similar discrepancies were reported in households with children as well (31% for self-reported vs. 6% for actual) 41 . Discrepancies were also observed in mask-wearing and social distancing, although that in hand disinfection 42 was particularly pronounced. Given that hand sanitization is less likely to disrupt friendships in children than mask wearing, the latter being a concern in psychological studies in terms of emotional recognition 9,[43][44][45] and cognitive performance 46 , replacing some of the mandates for mask-wearing and silent lunches with a greater promotion of hand sanitization might have been an alternative measure to balance the containment of COVID-19 infection and children's well-being.…”
Section: Discussionmentioning
confidence: 89%
“…Otherwise, the study was rated as medium methodological quality. In line with a systematic review which found that self-report methods of capturing adherence to protective behaviours can overestimate objectively observed adherence by up to a factor of five (13), any studies which employed a selfreport methodology were deemed not to satisfy the validty of outcome criterion, and so were necessarily limited to a quality score of medium or below. An additional reviewer independently assessed five of the studies, and conflicting findings were discussed.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (Effect of face covering use on adherence to other COVID-19 protective behaviours13…”
mentioning
confidence: 99%